Accompaniment For Healthy And Free From Anemia Teenagers In “M” Public Health Center Jember Regency - Umami, Riza; Jamhariyah, Jamhariyah (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Nutritional improvement in Indonesia focuses on 1000 first days of life which is connected with teenage’s nutrition state affecting to teenagers’ quality of life in reproductive ages and the next ages. Government attempts to prevent anemia through iron tablets supplementation for female teenagers as an effort to prepare them to be healthy mothers giving birth to high-quality children (Kemenkes RI, 2021). One of the midwifery services in the pandemic era includes the prevention of anemia in teenagers (Lorensia, 2020). This program aims to accompany teenagers to be healthy and free from anemia in the pandemic era, covers 42 teenagers (13 – 18 years old), and took place from June to July 2020 in the “M” public health center coverage area, Jember Regency. This program contains several events like FGD, education about reproductive health, hemoglobin test, iron tablets supplementation and multivitamins, consumption of iron tablets and multivitamins, and evaluation. The result is 98% of teenagers are not having anemia, 100% of teenagers are supplemented with iron tablets and multivitamins, and 98% of teenagers have a high level of knowledge about reproductive health, healthy lifestyle, and anemia. Suplementation of iron tablets should be done regularly and monitored to raise the teenager’s awareness about anemia.